Isolation of phytoconstituents and evaluation of biological potentials of Berberis hispanica from Algeria - Lemoui, Redouane; Benyahia, Samira; Noman, Labib; Bencherchar, Ilham; Oke-Altuntas, Feyza; Rebbas, Khellaf; Benayache, Samir; Benayache, Fadila; Demirtas, Ibrahim (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to isolate the phytoconstituents and evaluate the biological activities of Berberis hispanica. Three phenolic compounds (tamarixetin, caffeic acid and rutin) were isolated from B. hispanica. The structures of the pure compounds were elucidated by spectroscopic and mass-spectrometric analyses, including 1D-, 2D-NMR, and HPLC-TOF/MS. In addition, antimicrobial, anti-oxidant and anti-proliferative effects of the extracts, some fractions and isolated compounds were evaluated. The extracts of B. hispanica were evaluated against six bacterial strains and exhibited the highest activity against Klebsiella pneumonia (15 mm at 100 mg/mL). Fraction T36 (IC50<5 μg/mL) from the n-butanol extract displayed higher radical scavenging activity than butylated hydroxytoluene. The isolated compounds were evaluated for their antiproliferative effects against human cervical adenocarcinoma (HeLa) cell line by real time cell analyzer assay and tamarixetin exhibited the remarkable effect (IC50<50 μg/mL) on HeLa cells. This study supports the documented medicinal effects of B. hispanica. Video Clip of Methodology: Antiproliferative Assay: 4 min 31 sec Click to watch